Educación financiera para los estudiantes de bachillerato de la Unidad Educativa Manuel Ignacio Monteros Valdivieso - Correa Cabrera, Verónica Elizabeth (2022)
Financial education is an instructional process in which people, thanks to financial knowledge, seek to properly manage monetary resources by making correct decisions. The general objective of this research is to design a financial education program for high-school students of the "Manuel Ignacio Monteros Valdivieso" High School”; this program was developed based on a diagnosis of the participants’ level of financial knowledge. A quantitative and descriptive approach was applied in this study, and the sample consisted of 141 high-school students of a public high school. A survey of twenty-six questions was used as a research instrument for this investigation. The results show that, according to the standards of OECD's Programme for International Student Assessment (PISA), the participants of this study have a level three of knowledge regarding financial matters, which is average. In addition, this study shows that the design of a financial education program to strengthen the students’ knowledge is significant since the implementation of this program helped these learners reach a level five in terms of finances, which is a high level. Finally, it is concluded that this type of program is effective in strengthening the participants’ financial skills. It is also recommended that topics related to finances are included in the curriculum so when students reach adulthood, they will be able to plan their finances ideally